A novel cold active esterase from a deep sea sponge stelletta normani metagenomic library - Borchert, E.; Selvin, J.; Kiran, S.; Jackson, S.; O'Gara, Fergal; Dobson, A. (2017)
© 2017 Borchert, Selvin, Kiran, Jackson,O'Gara and Dobson. Esterases catalyze the hydrolysis of ester bonds in fatty acid esters with short-chain acyl groups. Due to the widespread applications of lipolytic enzymes in various industrial applications, there continues to be an interest in novel esterases with unique properties. Marine ecosystems have long been acknowledged as a significant reservoir of microbial biodiversity and in particular of bacterial enzymes with desirable characteristics for industrial use, such as for example cold adaptation and activity in the alkaline pH range. We employed a functional metagenomic approach to exploit the enzymatic potential of one particular marine ecosystem, namely the microbiome of the deep sea sponge Stelletta normani. Screening of a metagenomics library from this sponge resulted in the identification of a number of lipolytic active clones. One of these encoded a highly, cold-active esterase 7N9, and the recombinant esterase was subsequently heterologously expressed in Escherichia coli. The esterase was classified as a type IV lipolytic enzyme, belonging to the GDSAG subfamily of hormone sensitive lipases. Furthermore, the recombinant 7N9 esterase was biochemically characterized and was found to be most active at alkaline pH (8.0) and displays salt tolerance over a wide range of concentrations. In silico docking studies confirmed the enzyme's activity toward short-chain fatty acids while also highlighting the specificity toward certain inhibitors. Furthermore, structural differences to a closely related mesophilic E40 esterase isolated from a marine sediment metagenomics library are discussed.